Which Canal BPPV Should be Checked for Residual Disease after 1 Week? - Öner, Fatih (SAGE Publications, 2024)
Objectives: The study aimed to determine the residual disease rate due to the affected canal in patients diagnosed with benign paroxysmal positional vertigo (BPPV) and reveal the factors affecting the residual disease. Materials and Methods: A comprehensive investigation was conducted to determine the effect of the affected canal, sociodemographic data, body mass index, hospital admission time, systemic disease history, betahistine use, and previous otologic vertigo history on the residual BPPV rate. This investigation was carried out on 201 patients who underwent repositioning maneuvers with BPPV diagnosis and came for a follow-up 1 week later, ensuring a robust and reliable dataset. Results: Two hundred one patients were included in the study: 91 (45.3%) male and 110 (54.7%) female. The mean age of the patients was 60.44 + 13.83 (min = 23-max = 90) years. Residual disease was significantly higher in bilateral canal involvement ( P = .001), anterior canal involvement, and those presenting 72 hours after the onset of the vertigo attack ( P = .001). There was no significant difference between residual disease and those with successful initial maneuver results regarding age, gender, obesity, canalolithiasis, or cupulolithiasis. Conclusion: The most effective treatment for BPPV is canalith reposition maneuvers. We recommend that patients be called for follow-up after 1 week, especially in cases of anterior canal involvement and bilateral involvement. These findings provide valuable insights for the management of BPPV.
Keywords: Male; Adult; Aged, 80 and over; Time Factors; Middle Aged; Semicircular Canals; Patient Positioning; Young Adult; Humans; Female; Benign Paroxysmal Positional Vertigo; Aged